Implementasi Keamanan di Cloud Storage Menggunakan Algoritma Key Public Berdasarkan Block Cipher - Manik, Hazizah W.S; Utama, Huzefah; Irawan, Muhammad Dedi; Hafizd, Sefian Habil (Jurnal Sains dan Teknologi (JSIT), 2023)
Cloud computing is a new era of the modern world. It is an emerging paradigm and has become one of the hottest research to date, because of its ability to reduce the costs associated with computing. The main issues associated with cloud computing are data privacy, security and authenticity. The aim of the researcher is to find out how the model of cloud data storage and data security of cloud computing systems. In this research, researchers propose an efficient method for providing data storage. Security in cloud computing uses a new public key algorithm based on a linear block cipher. This algorithm has been proven by previous studies such as Data encryption, E-commerce, Digital signature. In research, researchers apply the same algorithm, namely cloud computing. In this algorithm several important security services are included such as key generation, encryption and decryption provided in the cloud computing system. The scope of this research is to solve security problems in cloud provisioning and cloud consumers by using new cryptographic methods.